2018
DOI: 10.1016/j.bbrc.2017.11.174
|View full text |Cite
|
Sign up to set email alerts
|

TR47, a PAR1-based peptide, inhibits melanoma cell migration in vitro and metastasis in vivo

Abstract: Activated Protein C (APC) is a serine-protease that displays antithrombotic and anti-inflammatory properties. In addition, cleavage of protease-activated receptor 1 (PAR1) by APC exerts endothelial cytoprotective actions. The effects of APC on endothelial cells may be reproduced by TR47, a PAR1-based peptide that mimics the novel N-terminus of PAR1 generated upon cleavage at Arg-46 by APC. In this study we demonstrate that wild-type APC and its signaling-proficient mutant, APC-2Cys (which has dramatically redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…49,50 Studies demonstrated that shortening the PAR1-derived peptide P1(47-66) to an 8-or 9-mer, respectively, retains cytoprotective activities. 22,51 Here, we show that a single mutation of Asn47 to…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…49,50 Studies demonstrated that shortening the PAR1-derived peptide P1(47-66) to an 8-or 9-mer, respectively, retains cytoprotective activities. 22,51 Here, we show that a single mutation of Asn47 to…”
Section: Discussionmentioning
confidence: 70%
“…Subsets of wells were selected and cells were treated for 60 minutes at 37°C in serum-free RPMI with: Although PAR3 itself is generally thought to be a nonsignaling receptor, it is speculated that PAR3 can modulate PAR1 signaling through PAR1:PAR3 dimerization. 24,[27][28][29] Thus, we hypothesized that although low concentrations of either P1 (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66) Figure 3A). Next, we sought to determine whether this reduction in caspase-1 activity by APC, PAR1, and PAR3 peptides might be conserved in human primary monocytes as it is known that APC can effect human primary monocytes.…”
Section: Essentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgenic mice overexpressing EPCR (Tie2-EPCR) had a 50–92% decrease in liver and lung metastases compared with wildtype animals. Additionally, treatment of the mouse with recombinant human APC or a signaling-proficient mutant, APC-2Cys (with reduced anticoagulant activity), also led to a reduction of metastatic melanoma foci by inhibiting transendothelial migration of malignant cells [11,48]. The APC/EPCR interaction, e.g., in melanoma cells, likely decreases expression of endothelial adhesion molecules, such as P-selectin that is essential for tumor cell-endothelium interactions during extravasation, ultimately hindering dissemination [11].…”
Section: Epcr and Cancermentioning
confidence: 99%